Pembuatan dan Karakterisasi Biodiesel dan Crude palm Oil (CP0) dan Limbah Kondensat dengan Katalis NaOCH 3 - Erna, Maria; Testiaty, Ety; Manik, Oskar M. (Jurnal Pilar Sains, 2006)
This research produced bi isel from Crude Pin 0 (çPQ) and ccdensate waste which their productionsincreased every year. Biodiesel was friendly to environment and it could be directly used on dieselengines. Biodiesel was produced with transesterification reaction between triglycerides and methanol,and it was added with catalyst of NaOCH3. This research resulted that biodiesel produced from CPOapproached standard characteristic: density of 0.8613 gr/nil and viscosity of 5.4474 cP. Then,biodiesel produced from mixture between condensate waste and CPO was far enough from standardcharacteristic.